The Influence of Corporate Characteristics on Tax Avoidance and Corporate Tax Disclosure: evidence from manufacturing companies listed on the indonesia stock exchange (idx) from 2018 to 2022 - Kalam Al Iqbal; Evita Puspitasari (Britain International for Academic Research (BIAR) Publisher, 2026)
Objective – This study investigates the impact of company characteristics on tax avoidance and tax disclosure in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018–2022 period. This research is a type of quantitative research with a causal study design. Based on nonprobability sampling with a purposive sampling approach, a sample of 76 companies with a period of 5 years was obtained, so there were 380 observations. The data analysis method used in this study is panel data regression analysis with Microsoft Excel 2019 software and EViews 13.0 as the analysis tool. Based on the results of research and discussion, researchers can conclude that profitability has a positive and significant effect on tax avoidance, which indicates that the higher the company's profitability, the more likely the company is carry out strategies to reduce its tax liability. However, size and leverage have a positive but not significant effect. Thus, the size and level of corporate debt do not significant. Furthermore, profitability, size, and leverage have a positive and significant effect on tax disclosure both partially and simultaneously. That is, companies that are more profitable, larger, and have higher debt tend to be more transparent in disclosing their tax information. This suggests that these factors influencing the extent to which companies are willing to disclose their taxation information (p<0.05 value). this study only conducted on manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period did not use control variables as other variables that can affect tax avoidance and tax disclosure. This study provides information that to minimize tax avoidance intentions on Corporate Taxpayers, the tax officer can analyze the company characteristics on ROA financial performance, size, and leverage. Conduct an internal analysis of the company's financial performance and capital structure. Review ROA rates, company size, and leverage ratios periodically to understand how these variables correlate with tax policy. Provide education and training to finance and management teams on the role of ROA, size, and leverage in tax policy. Ensure a better understanding of how these variables affect a company's tax outcome.